Pemberdayaan Kelompok Wanita Tani dalam Pemanfaatan Mikro Organisme Lokal Hasil Limbah Rumah Tangga untuk Pertanian: Empowerment of Women Farming Groups in Utilizing Local Micro Organisms from Household Waste for Agriculture - Angreza, Riyank Dicky; Sulkifli, Sulkifli; Yusuf, Andi Cakra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Bonto Karaeng Village is known as one of the most important sectors with people's livelihoods as livestock breeders, farmers, and traders which means that residents do not lack food. However, the household waste produced has not been utilized properly, resulting in significant environmental pollution. Therefore, this activity was carried out to empower and provide knowledge to the community about managing household waste into Local Microorganisms (MOL) which is useful for improving soil fertility and better quality of harvest. The method used was counseling and training which was attended by a group of women farmers in Bonto Karaeng Village. With this training, the community, especially women farming groups, are expected to get the results they hope for. They understand how to manage household waste combined with EM4 to make MOL and it is hoped that this activity can handle existing household waste by making it more useful.